The Mystery of Madness - Coles, Robert (The Hastings Center report, 1982)
Book reviewed in this article: Mystical Bedlam: Madness, Anxiety, and Healing in Seventeenth Century England. By Michael MacDonald. Making It Crazy: An Ethnography of Psychiatric Clients in an American Community. By Sue E. Estroff. Mind, Mood, and Medicine: A Guide to the New Biopsychiatry. By Paul H. Wender, M.D. and Donald F. Klein, M.D.